UMMATAN WASAṬAN PERSPEKTIF MUFASIR KONTEKSTUALIS INDONESIA SEBAGAI RESOLUSI KONFLIK KEKERASAN KOMUNAL - Nugroho, Sapta Wahyu (Institut PTIQ Jakarta, 2020)
This study aims to explain and then compare the interpretations of two Indonesian contextualize commentators, namely Hamka and M. Quraish Shihab about the wasaṭan ummatan in the Koran. This research is driven by the writer's concern about radical and extreme attitudes that lead to various communal violent conflicts in contemporary socio-religious life that still often occur in the lives of Muslims. With the comparative method, this research will show the similarities and differences in the methods and substance of the interpretations of the two figures, as well as indicators of wasaṭan ummah and their relevance in answering problems. The ummatan wasaṭan indicators formulated from the two commentators are: 1) Maintaining the importance of a balance between the attainment of the world and the attainment of the hereafter, maintaining the quality of his relationship to God in ukhrawi milk and harmony among fellow humans in the worldly side. 2) Emphasize fair and moderate traits. wise, careful, and more thorough in seeing the various problems that are accepted by him. 3) Being careful and holding firmly to the principle of shiraṭal mustaqim as a condition of the ummatan wasaṭan. The wasaṭan community can be a solution to various problems that contain extremities, including the primordial fanaticism which is the base of communal conflict, if it is supported by every element of society, the state and religion